Status of the “Nord Stream” according to European Union Law - Moskwa Urszula (Московский журнал международного права)
In 2000, the European Commission has recognized, passing through the Baltic Sea «Nord Stream» project part of the Trans-European energy network. In September 2006, the Commission stated that it was one of the energy projects of the highest priority of the European Union, which is in the interests of the whole Europe. In 2006, the European Commission, the European Parliament and the European Council recognized the pipeline project as a project of European interest. This article explains the meaning of projects of common interest (priority projects, projects of European interest) in accordance with Decision No 1364/2006/EC of the European Parliament and of the Council of 6 September 2006 and Regulation (EU) No 347/2013 of the European Parliament and of the Council of 17 April 2013.